1988
DOI: 10.1029/wr024i010p01711
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic analysis of solute arrival time in heterogeneous porous media

Abstract: Longitudinal advective solute movement in heterogeneous porous media is investigated by considering the solute arrival time at a plane perpendicular to the mean fluid velocity. The moments of the solute arrival time are defined in terms of the stochastic properties of a statistically anisotropic hydraulic conductivity field. The flux-averaged concentration is specified by introducing the moments of the arrival time into a probability density function for the arrival time. The quadratic dependence of the arriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 13 publications
2
162
0
Order By: Relevance
“…The temporal moments in Table 1 Table 2). The mean arrival time for the uniform injection mode is the travel distance divided by the harmonic mean velocity, a result commonly associated with "instantaneous" injections into stratified systems [e.g., Shapiro and Cvetkovic, 1988]. However, injection in flux yields a mean arrival time equal to travel distance divided by arithmetic mean velocity.…”
Section: Solutions For Flux Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal moments in Table 1 Table 2). The mean arrival time for the uniform injection mode is the travel distance divided by the harmonic mean velocity, a result commonly associated with "instantaneous" injections into stratified systems [e.g., Shapiro and Cvetkovic, 1988]. However, injection in flux yields a mean arrival time equal to travel distance divided by arithmetic mean velocity.…”
Section: Solutions For Flux Detectionmentioning
confidence: 99%
“…In particular, spatial variability in groundwater velocity caused by hydraulic conductivity heterogeneity is generally regarded as the most important mechanism that induces spreading at the field scale [e.g., Dagan, 1989]. This advection-dominated nature of nonreactive solute transport has lead to the development of stochastic-advective approaches to transport modeling, which have followed richly diverse paths [e.g., Simmons, 1982;Dagan, 1984;Shapiro and Cvetkovic, 1988;Charbeneau, 1988;Jury and Roth, 1990]. These different development paths share the notion that larger-scale velocity variability dominates spreading and that local dispersion may be neglected in modeling average longitudinal transport.…”
Section: Introductionmentioning
confidence: 99%
“…If the flow regions are non-interacting, meaning that the boundaries of each region are impermeable for particles, an individual particle remains for its entire travel time within the region it entered. This mechanisms leads to a process which is called stochastic-advective and has often been used to analyze solute transport (e.g., Dagan and Bresler, 1979;Jury, 1982;Simmons, 1982;Shapiro and Cvetkovic, 1988). If a particle can move laterally through the boundary of its flow region, it experiences the velocities of other flow regions.…”
Section: Local Velocity Distribution and Flow Regimementioning
confidence: 99%
“…Stochastic-advective transport models can be regarded as special cases of multiple region models with noninteracting regions (e.g., Dagan and Bresler, 1979;Jury, 1982;Simmons, 1982;Shapiro and Cvetkovic, 1988). Although lateral mass exchange is neglected, longitudinal spreading of a pulse is achieved by choosing an appropriate shape of the velocity distribution as shown in Fig.…”
Section: Multiple Flow Regions Without Mass Exchangementioning
confidence: 99%
“…Temporal moments have been used for the characterization of conservative transport in heterogeneous aquifers by various authors [Shapiro and Cvetkovic, 1988 [1997] showed that the impact of local-scale dispersion on the second central moment of the integrated breakthrough curve is small for most practical cases and may be even less for kinetically sorbing solutes.…”
Section: Paper Number 1999wr900354mentioning
confidence: 99%